Enhancing critical thinking skills and media literacy in initial VET students: A mixed methods study on a cross-country training program - Francesco Tommasi; Andrea Ceschi; Sara Bollarino; Silvia Belotto; Silvia Genero; Riccardo Sartori (International Journal for Research in Vocational Education and Training (IJRVET), 2023)
Context: In the last few decades, the constant and exponential changes in the society's consumption of information have increased the awareness of practitioners from the education and training field, on the need for training programs for the enhancement of critical thinking skills and media literacy among students from Initial Vocational Education and Training (IVET) who are less exposed to intellectual trainings than their peers in traditional education pathways. Approach: With this impetus, the present paper reports the results of a mixed methods study evaluating a training program for such competences. Based on a cognitive psychology theoretical framework, the training program consisted in three main techniques through which trainers can work with students in the classroom. N= 35 trainers from five different countries (i.e., Greece, Italy, Spain, Portugal, and the Netherlands) were instructed about the training techniques and implemented them in their training centres. Then, a total of N= 288 students among these countries were involved in the testing of the training, which took place on a duration average of 5 months. Mixed methods approach was used to evaluate the effectiveness and quality of the training. Notably, prospective statistical analysis evaluated the training's impact of the participating students and compared with a control group. Qualitative interviews examined the training's lived experience with a group of students and trainers. Findings: The quantitative and qualitative analysis of pre/post- measures of critical thinking skills and media literacy of the experimental group, and the comparison with the control group, indicate an increase in these competences and confirm the efficacy of the training intervention. Conclusion: These results inform about the usefulness of the training program cross-culturally and the feasibility of training strategies based on cognitive psychology. Moreover, the paper offers a methodological contribution thanks to the proposition of the mixed methods approach for training programs assessment.
urn:nbn:de:gbv:18-10-1087-7
Keywords: 330; Critical Thinking Skills; Social Media; Educational Program; Qualitative Research; Quantitative Research; VET; Vocational Education and Training